Narratives of the Medieval Deccan: Kannada Literary Heritage and Historical Imagination in India - Lata N. Killedar (ಅಕ್ಷರಸೂರ್ಯ (AKSHARASURYA), 2026)
This article examines the narrative strategies and cultural functions of Kannada literary production in the medieval Deccan, arguing that these texts played a vital role in shaping historical imagination and regional identity. Drawing on a close reading of epics, hagiographies, courtly chronicles, and inscriptional poetry, the study traces how authors and patrons used storytelling techniques mythic interpolation, genealogical framing, and Syncretic historiography to negotiate political legitimacy, social hierarchies, and communal memory. Attention is given to the interplay between oral performance and written text, and to the ways vernacular Kannada reworked Sanskritic paradigms to address local concerns: landholding, temple patronage, and the sacralization of rulers. Methodologically, the article combines literary analysis with historical contextualization, using comparative readings of selected manuscripts and epigraphic evidence to reconstruct how narrative forms mediated historical knowledge for diverse audiences. The findings suggest that medieval Kannada narratives were not passive reflections of events but active agents in producing a layered historical consciousness—one that could legitimize dynasties, circulate moral norms, and accommodate cultural pluralism across the Deccan.